Autour de quelques valeurs de be to en anglais contemporain - Eric Gilbert (Studii de Lingvistica)
In most grammars, be to is treated as a modal periphrasis or construction, whose various interpretations derive from a primary semantic value, differing from one grammarian to another, which suggests the limits of such an approach. It appears in fact more fruitful to adopt a compositional approach and analyse be to as resulting from the combination of two distinct operations, the central one marked by be, and the background one marked by to, each of which, depending on the context, will contribute to the semantic value of the whole. The proposed approach will fall within the framework of the Theory of Enunciative Operations and will focus on three of the main values of the combination: arrangement/project, constraint/obligation and intention.